(untitled) (Proceedings of the International Conference on Public Health, 2026)
To safeguard human health food safety is indispensable. Food safety oversight, which is widespread in expanding informal food sector, causes concern. Hence, the overall objective of this study was to “investigate the level of knowledge and practices on food safety amongst street food vendors in the Durban Central Business District, South Africa”. The investigation was conducted using a descriptive cross-sectional study design, with non- probability convenience sampling utilised to recruit respondents. Three hundred and sixty (360) street food vendors who were selling vendor-cooked foods constituted the research population. The data was collected using a structured questionnaire that was administered by an interviewer. The questionnaire was adapted from similar studies conducted previously. The gathered data was analysed using Statistical Package for Social Sciences version 29 software. In South Africa, hot foods must have a core temperature of ≥+600C while in storage, in transit, or exhibition for sale. Only 23.9% (86) of respondents knew this. Likewise, chilled foods must have a core temperature of ≤+50C while in storage, in transit, or shown for sale. However, only 14.7% (53) of respondents knew this requirement. In reference to water safety, only 42.2% (152) of respondents were aware that water which is safe for use cannot be identified by its appearance. Approximately 14.7% (53) of respondents agreed that alteration in appearance, scent, and flavour does not always have to occur in food that has been contaminated. Concerning practices, only 8.9% (32) of respondents washed their hands with soap and running water. Approximately 51.5% (185) of respondents do not engage in handling food whilst handling cash. A minority of respondents (11.1%, 40) used warmers to keep cooked food. Regarding water safety, distinctive attributes of contaminated food, and storage temperatures street food vendors still lack essential knowledge. It is therefore necessary that street food vendors receive training.